(untitled) (Contemporary Journal of Social Science Review, 2025)
Aiming to explore the language learning process among the students with special needs, the current study endeavoured to examine the relationship between the willingness to write and writing proficiency among visually impaired computer-literate Pakistani ESL learners. The sample comprised 28 visually impaired students selected through purposive sampling. The data comprised scores from participants’ argumentative essay compositions and their responses on the WTW questionnaire measuring willingness to write. Kendall’s Tau, a nonparametric statistical test, was employed to examine the correlation between writing proficiency and WTW. The results revealed a very weak, negative, and nonsignificant correlation between WTW and writing proficiency (Kendall’s Tau = –.122, p > .05). The study contributes to the existing body of knowledge by highlighting the limited role of willingness to write in predicting writing proficiency among visually impaired learners. These findings may inform curriculum developers and pedagogy specialists in designing materials and strategies that go beyond motivational aspects, focusing instead on practical support to enhance writing skills. The study may also serve as a reference point for future researchers exploring the language learning journey of differently abled students.